2020
DOI: 10.1029/2019ms001886
|View full text |Cite
|
Sign up to set email alerts
|

The Global Land Carbon Cycle Simulated With ISBA‐CTRIP: Improvements Over the Last Decade

Abstract: We present the latest version of the ISBA‐CTRIP land surface system, focusing on the representation of the land carbon cycle. We review the main improvements since the year 2012, mainly added modules for wild fires, carbon leaching through soil and transport of dissolved organic carbon to the ocean, and land cover changes but also improved representation of photosynthesis, respiration, and plant functional types. This version of ISBA‐CTRIP is fully described in terms of land carbon pools, fluxes, and their int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 126 publications
(239 reference statements)
1
45
0
Order By: Relevance
“…Future analyses of the deforest-glob experiments could further focus on the seasonality of vegetation and climate variables (e.g. with regard to large-scale atmospheric circulation changes) to advance the understanding compared to previous studies (Bonan, 2008;Chen and Dirmeyer, 2020;Davin and de Noblet-Ducoudré, 2010;de Noblet-Ducoudré et al, 2012;Pitman et al, 2009). Additionally, the enhanced meridional temperature gradient may alter the large-scale atmospheric circulation that deserves future explorations.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Future analyses of the deforest-glob experiments could further focus on the seasonality of vegetation and climate variables (e.g. with regard to large-scale atmospheric circulation changes) to advance the understanding compared to previous studies (Bonan, 2008;Chen and Dirmeyer, 2020;Davin and de Noblet-Ducoudré, 2010;de Noblet-Ducoudré et al, 2012;Pitman et al, 2009). Additionally, the enhanced meridional temperature gradient may alter the large-scale atmospheric circulation that deserves future explorations.…”
Section: Discussionmentioning
confidence: 97%
“…With prescribed SSTs the mediating effect of the ocean on the land temperatures is missing, resulting in overestimated tropical warming and underestimated boreal cooling over deforested areas (Davin and de Noblet-Ducoudré, 2010).This setup assumes that the effect of large-scale circulation changes is small and can be ignored. Climatic effects of historical land use and land cover changes (LULCCs) studied in this setup show substantial differences among global climate models due to differences in land surface schemes and their implementation of changes in land cover to represent deforestation (Boisier et al, 2012;de Noblet-Ducoudré et al, 2012;Pitman et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Ocean carbon cycle is represented using the Canadian Model of Ocean Carbon (CMOC) which was developed for earlier versions of CanESM (Arora et al, 2011;Christian et al, 2010), and between the atmosphere, the ocean, the lakes and the land surface. Over the land surface, CNRM-ESM2-1 uses the ISBA-CTRIP land surface modeling system (http://www.umrcnrm.fr/spip.php?article1092&lang=en) to solve energy, carbon and water budgets at the land surface (Decharme et al, 2019;Delire et al, 2019). Its physical core explicitly solves the one- of the leaves.…”
Section: A53 Canadian Centre For Climate Modelling and Analysis (Ccmentioning
confidence: 99%
“…This dissolved organic carbon is transported by the rivers to the ocean. A detailed description of the terrestrial carbon cycle can be found in Delire et al (2019).…”
Section: A53 Canadian Centre For Climate Modelling and Analysis (Ccmentioning
confidence: 99%
“…The most significant results show improvements in the river discharge simulations, the snowpack representation and the land surface evapotranspiration (Decharme et al, 2019). Recently, the updated version of ISBA-CTRIP, considering improvements such as wild fires and land cover changes (Séférian et al, 2019), has also shown a better representation of global-scale carbon pools and fluxes (Delire et al, 2020).…”
Section: Isba-ctrip Systemmentioning
confidence: 99%